2008
DOI: 10.1111/j.1745-7254.2008.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGF-β1 antisense oligodeoxynucleotide on renal function in chronic renal failure rats

Abstract: Aim: The aim of the present study was to investigate the effectiveness of transforming growth factor (TGF)-β1 antisense oligodeoxynucleotides (ODN) in ameliorating deteriorated kidney function in rats with puromycin-induced chronic renal failure (CRF). Methods: Saline, puromycin, puromycin+TGF-β1 antisense ODN or puromycin+scrambled ODN were administered to unilaterally nephrectomized rats. Renal hemodynamic and excretory measurements were taken in the anaesthetized rats that had undergone surgical procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Even though TGF beta1 is typically known to be an inhibitor of cell growth, authors consider that it prevents only the synthesis of DNA and cell proliferation, but promotes mRNA and protein synthesis, therefore enhancing cell hypertrophy. Hiong et al [50] showed that, in rats, treatment of chronic renal failure with TGF beta1 antisense oligodeoxynucleotides (ODNs) prevented hypertrophy of the kidneys, probably due to the suppression of the extracellular matrix accumulation in the kidney. TGF beta1 antisense ODN treatment reduced kidney weight in diabetic mice with kidney hypertrophy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Even though TGF beta1 is typically known to be an inhibitor of cell growth, authors consider that it prevents only the synthesis of DNA and cell proliferation, but promotes mRNA and protein synthesis, therefore enhancing cell hypertrophy. Hiong et al [50] showed that, in rats, treatment of chronic renal failure with TGF beta1 antisense oligodeoxynucleotides (ODNs) prevented hypertrophy of the kidneys, probably due to the suppression of the extracellular matrix accumulation in the kidney. TGF beta1 antisense ODN treatment reduced kidney weight in diabetic mice with kidney hypertrophy [51].…”
Section: Discussionmentioning
confidence: 99%
“…In CKD cats, urinary TGF-b1 levels (TGF-b1/creatinine ratio) were dramatically up-regulated and could be used as a clinical marker for disease progression (Arata et al, 2005). It was showed that impaired renal function and the deterioration in morphology was in part dependent upon the action of TGF-b1 within the kidney in CKD model rats (Hiong et al, 2008). Previous epidemiological studies implicated three common single nucleotide polymorphisms (SNPs) in the TGF-b1 gene, namely rs1800469 (C509T), rs1800470 (T869C), and rs1800471 (G915C) in the susceptibility to CKD.…”
Section: Discussionmentioning
confidence: 99%
“…As a transduction molecule, mothers against decapentaplegic (Smad) protein transduces TGF-β1 family signals to the nucleus. The TGF-β1/Smad pathway is a final and common pathway of renal fibrosis (24). In the TGF-β1/Smad signaling pathway, an active transcription complex produced by Smad2/3 enters the nucleus while Smad6 inhibits the transduction of TGF-β1 signals (25).…”
Section: Discussionmentioning
confidence: 99%